A Inﬂuência de Mídias Multissensoriais na Aprendizagem de Crianças com Dislexia - Silva, Ellen Paixão; Amorim, Glauco; Santos, Joel dos (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2021: Anais Estendidos do XXI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2021.16103, 2021)
Studies published in the literature indicate that the use of multimedia content improves the reading performance of students with dyslexia. However, most multimedia applications use only two of the ﬁve human senses. MBook, a multisensory book developed for this work, uses an eye tracker to synchronize wind, smell, sounds, and light effects to the text being read. It was based on the hypothesis that a multisensory reading could reduce the overload in working memory, thus improving comprehension. Experimental results point to a gain in text comprehension and an increase in reading speed by the student with dyslexia when multisensory media were used. Also, the use of the tool pointed to an increase in reading motivation.